FORECASTING REGARDING CAR FUEL IN RUSSIA THROUGH EXPERT EVALUATION AND TREND EXTRAPOLATION - Elena E. Shidakova (Вестник Северо-Кавказского федерального университета)
The article focuses on the theoretical aspects of economic foresting. There is a detailed investigation into the models and methods for forecasting with a selection offered that is the most relevant in view of the topic. There is also an estimation of a potential change in the average prices for the most popular fuels, which is done through expert evaluation and trend extrapolation.